Antibodies to the conserved cytoplasmic domain of the integrin beta 1 subunit react with proteins in vertebrates, invertebrates, and fungi (The Rockefeller University Press, 1988)
The integrin family of cell surface receptors can be divided into three groups on the basis of their homologous beta subunits: beta 1, beta 2, and beta 3. We have raised an antibody against a synthetic peptide corresponding to the COOH-terminal domain of the chicken integrin beta 1 subunit that reacts with beta subunits from a variety of vertebrates, invertebrates, and fungi, demonstrating strong evolutionary conservation of sequences in this domain. In Drosophila cells, the antibody recognizes integrin alpha beta complexes that appear to be identical with position-specific antigens. Cross-reactive proteins are also detected in Caenorhabditis elegans and Candida albicans. The antiserum is specific for beta 1 subunits and does not recognize other integrin beta subunits in humans. In immunofluorescence analyses of cultured cells, the antibody reacts only with permeabilized cells confirming that this highly conserved COOH-terminal segment is a cytoplasmic domain.